PENGARUH GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. TIRTA SARI KABUPATEN INDRAGIRI HULU - Marwan Indra Saputra (LPPM Press STIE Indragiri Rengat, 2018)
This research was conducted on PT. Tirta Sari Indragiri Hulu Regency with the aim to determine the influence of Leadership Style and Organizational Climate variables on Employee Performance at PT. Tirta Sari, Indragiri Hulu Regency. Sampling was done by accidental sampling method with 146 samples as respondents. The analytical method used is quantitative descriptive, data analysis is carried out simultaneously (multiple linear regression analysis with the help of IBM SPSS Stastic version 21.0. From the results of the study, the regression equation obtained is Y = 6.313 + 0.143X1 + 0.242X2, it can be seen that the Leadership Style and Organizational Climate have a positive influence on Employee Performance at PT. Tirta Sari, Indragiri Hulu Regency. In addition, simultaneous testing (Test F), has obtained F count > F table that is equal to 8.738 > 3.06. So that the two independent variables namely Leadership Style and Organizational Climate together have a positive and significant effect on the dependent variable, namely Employee Performance at PT. Tirta Sari, Indragiri Hulu Regency. While the Partial Regression Test (t test) shows that the dominant Climate Organization variable has a significant effect on Employee Performance at PT. Tirta Sari, Indragiri Hulu Regency, which is t count> t table of 3.394> 1.97658. While the leadership style variable has a significant effect on employee performance at PT. Tirta Sari, Indragiri Hulu Regency, which is t count > t table of 2.037 > 1.97658. In addition, the result of the multiple correlation coefficient is 0.330 which shows the level of the relationship between all independent variables to the dependent variable in this study is in the criteria of the weak relationship. The amount of influence caused by these two variables together affects the variable Employee Performance with a percentage of 10.9%. While 89.1% was influenced by other factors that did not participate in this study.